"Bariatricus massiliensis" as a new bacterial species from human gut microbiota. (July 2016) - Bessis, S.; Amadou, T.; Dubourg, G.; Raoult, D.; Fournier, P.-E.
Abstract: We report here the main phenotypic characteristics of "Bariatricus massiliensis" strain AT12 (CSUR P2179), isolated from the stool of a 58-year-old woman who underwent bariatric surgery.